2002
DOI: 10.1055/s-2002-34001
|View full text |Cite
|
Sign up to set email alerts
|

Stoßwellentherapie bei therapieresistenter Plantarfasziitis mit Fersensporn: eine prospektiv randomisiert plazebokontrollierte Doppelblindstudie

Abstract: The results of this study corroborate the value of ESWT for recalcitrant plantar fascitis. As a non invasive technique with low side effects, it can complement the row of conservative treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 1 publication
1
21
1
Order By: Relevance
“…Two of these were translated from German into English [21,22]. Four trials [23-26] were excluded from the review: in one, the intervention and control groups were treated at different time points making valid comparisons of patient outcomes in both groups impossible [24].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Two of these were translated from German into English [21,22]. Four trials [23-26] were excluded from the review: in one, the intervention and control groups were treated at different time points making valid comparisons of patient outcomes in both groups impossible [24].…”
Section: Resultsmentioning
confidence: 99%
“…Eleven RCTs were included in this review and they reported data published between 1996–2003 from trials involving 1290 patients [10-12,21,22,27,28,30-33]. Table 1 shows the quality assessment scores and Table 2 and Table 3 the baseline data.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations